Characterization of a Novel Dioxomolybdenum Complex by Cyclic Voltammetry - Knittl E. T. Esther Theresa; Rusakov D. A. Dmitry Aleksandrovich; Korotkova E. I. Elena Ivanovna; Dorozhko E. V. Elena Vladimirovna; Voronova O. A. Olesya Aleksandrovna; Plotnikov E. V. Evgeny Vladimirovich; Topaloglu-Sozuer I. Isil; Linert W. Wolfgang (2015, 2015)
Title screen